A trifunctional self-immolative spacer enables drug release with two non-sequential enzymatic cleavages. Issue 63 (15th July 2021) - Dal Corso, Alberto; Arosio, Simone; Arrighetti, Noemi; Perego, Paola; Belvisi, Laura; Pignataro, Luca; Gennari, Cesare
Abstract : The enzymatic dephosphorylation of a self-immolative spacer accelerates cargo release and acts as an additional and independent trigger in protease-sensitive prodrugs. Abstract : Cyclative cleavage of an amine-carbamate self-immolative spacer to deliver a hydroxyl cargo was inhibited by spacer derivatisation with a phosphate monoester handle. This trifunctional spacer was installed in a model anticancer prodrug that showed fast drug release only when incubated with both a protease and a phosphatase enzyme.